The effect of cross-rolling on the growth of goss grains in a grain oriented silicon steel - Citrawati, F.; Quadir, Md Zakaria; Munroe, P. (2016)
© 2016, Springer International Publishing AG. All rights reserved. A series of cross-rolled cold rolling experiments, followed by annealing experiments, were carried out on a commercial two-pass cold rolled Fe-Si alloy. Even though no major influence was observed on the primary recrystallized grains after the sheet was subjected to ~10% deformation, its effect on the texture distribution of the sheet (prior to annealing) is noticeable. The texture of the rolled sample showed increases in the {112}<111> orientation and Goss texture within a 5° spread. However, after annealing for 10 and 60 min. at 900°C, abnormal growth of Goss grains does not occur and the Goss texture gradually disappears.